Neuroplastic changes in c‐Fos, ΔFosB, BDNF, trkB, and Arc expression in the hippocampus of male Roman rats: differential effects of sexual activity. Issue 7 (18th June 2022) - Sanna, Fabrizio; Serra, Maria Pina; Boi, Marianna; Bratzu, Jessica; Poddighe, Laura; Sanna, Francesco; Carta, Antonella; Corda, Maria Giuseppa; Giorgi, Osvaldo; Melis, Maria Rosaria; Argiolas, Antonio; Quartu, Marina
Abstract: Sexual activity causes differential changes in the expression of markers of neural activation (c‐Fos and ΔFosB) and neural plasticity (Arc and BDNF/trkB), as determined either by Western Blot (BDNF, trkB, Arc, and ΔFosB) or immunohistochemistry (BDNF, trkB, Arc, and c‐Fos), in the hippocampus of male Roman high (RHA) and low avoidance (RLA) rats, two psychogenetically selected rat lines that display marked differences in sexual behavior (RHA rats exhibit higher sexual motivation and better copulatory performance than RLA rats). Both methods showed (with some differences) that sexual activity modifies the expression levels of these markers in the hippocampus of Roman rats depending on: (i) the level of sexual experience, that is, changes were usually more evident in sexually naïve than in experienced rats; (ii) the hippocampal partition, that is, BDNF and Arc increased in the dorsal but tended to decrease in the ventral hippocampus; (iii) the marker considered, that is, in sexually experienced animals BDNF, c‐Fos, and Arc levels were similar to those of controls, while ΔFosB levels increased; and (iv) the rat line, that is, changes were usually larger in RHA than RLA rats. These findings resemble those of early studies in RHA and RLA rats showing that sexual activity influences the expression of these markers in the nucleus accumbens, medial prefrontal cortex, and ventral tegmental area, and show for the first time that also in the hippocampus sexual activity induces neural activation and plasticity, events that occur mainly during the first phase of the acquisition of sexual experience and depend on the genotypic/phenotypic characteristics of the animals.